2013
DOI: 10.1039/c3ra42510j
|View full text |Cite
|
Sign up to set email alerts
|

Optical stretching as a tool to investigate the mechanical properties of lipid bilayers

Abstract: Measurements of lipid bilayer bending modulus by various techniques produce widely divergent results. We attempt to resolve some of this ambiguity by measuring bending modulus in a system that can rapidly process large numbers of samples, yielding population statistics. This system is based on optical stretching of giant unilamellar vesicles (GUVs) in a microfluidic dual-beam optical trap (DBOT). The microfluidic DBOT system is used here to measure three populations of GUVs with distinct lipid compositions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…The setup uses the diverging beams from two optical fibers to trap and stretch a GUV in a microfluidic channel. We have used the DBOT to measure GUVs with different lipid compositions [2]. We found that gel-phase membranes are significantly stiffer than liquid-phase membranes, consistent with previous reports.…”
Section: Measurements Of Mechanical Properties Of Cell Membranes In Asupporting
confidence: 82%
“…The setup uses the diverging beams from two optical fibers to trap and stretch a GUV in a microfluidic channel. We have used the DBOT to measure GUVs with different lipid compositions [2]. We found that gel-phase membranes are significantly stiffer than liquid-phase membranes, consistent with previous reports.…”
Section: Measurements Of Mechanical Properties Of Cell Membranes In Asupporting
confidence: 82%
“…As in our previous work measuring steady-state elastic deformation of lipid bilayers, 18,19 GUVs in an aqueous solution were flowed through a square glass capillary tube to a position between two laser diode-coupled optical fibers, where each vesicle was trapped and stretched via optical forces. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 This experiment covered the same range of applied laser powers as used in the previously described step power experiment. In the regime where bilayer deformation is dominated by bending modes, there is a log-linear relationship between applied tension and area strain.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 However, in general, thermodynamic and mechanical characterization requires separate experimental setups which constitute a serious limit for a high throughput analysis. Previous studies [22][23][24] on the deformation of vesicles in an OS were conducted with low power 808 nm laser diodes, in which heating effects were not considered. Such temperature effects have been characterized in optical tweezers 12 and in dual-beam laser traps 13 for a specific, commonly used wavelength (1064 nm).…”
Section: Introductionmentioning
confidence: 99%